Interactions between Benzo(a)pyrene exposure and genetic polymorphisms of AhR signaling pathway on missed abortion - Liu, Sha; Han, Mei; Zhang, Jiayu; Ji, Jingru; Wu, Yanfei; Wei, Junni (International journal of environmental health research, 2023)
Benzo(a)pyrene (BaP) is an environmental pollutant widely exposed to human beings. While the relationship between BaP and missed abortion is few understood. To explore the association between missed abortion and BaP, genetic polymorphisms of AhR pathway, we recruited 112 cases women with missed abortion and 137 controls women with normal pregnancy from Shanxi, China. The BPDE-DNA adducts level in the case group was higher than that in the control group (P < 0.001). The subjects were categorized according to the tertiles of BPDE-DNA adduct concentrations: T 1 (<P 33 ), T 2 (P 33 ~P 67 ) and T 3 (≥P 67 ), the results suggested that the risk of missed abortion at T 2 and T 3 levels were 5.68 times (P = 0.009), 6.17 times (P = 0.001) higher than that of T 1 level, respectively. The interaction between ALDH3A1 rs887241 and BPDE-DNA adducts was indicated. These findings show that BaP exposure may affect the risk of missed abortion, and genetic polymorphisms may change the susceptibility to BaP.